Dementis. A drawing that realized - Maurial Chávez, Ivan (2013)
The author of “Dementis, a drawing that realized,” tells his central experiences around the character.He proposes Dementis as a figure that summarizes the key elements to understand the essentialof human: its ability to rebuild their own plot and its ability to take distance itself through sense ofhumor. Dementis enter into the psychotherapeutic topic as the representative image of the manwho in spite of suffering makes a creatively breaks with the rigidity of the affections. Rosa Carrascoperforms a deep linguistic analysis and content of the work that places Dementis like a book richin meanings, comparing with important characters of the world literature.